PODKESAD sebagai upaya Pencegahan Risiko Stunting pada KAT - safitri, safitri; Maharani, Sri; Fatmawati, Tina Yuli; Asparian, Asparian; Lisna, Lisna (Universitas Baiturrahim, 2025)
Indigenous Communities (KAT) are still an issue in Indonesia and local governments. KAT in Jambi Province are spread across several regencies, sub-districts and villages. One of them is in Hajran Village, Batanghari Regency. KAT has complex social problems, namely poverty, education and health. Health problems in KAT arise due to the low implementation of Clean and Healthy Living Behavior (PHBS) because this behavior is not yet understood. Increased knowledge and changes in PHBS occur after education is provided. Pop-up book media can increase knowledge, attitudes, skills and behavior of PHBS. Increasing awareness of PHBS as a strategy for preventing stunting. In Hajran Village in June 2024, there were 5 cases of stunting and 2 cases of malnutrition. The Suku Anak Dalam Health Education Center (PODKESAD) is an application of technology development and innovation as an effort to prevent the risk of stunting. This activity aims to increase knowledge and behavior of PHBS in KAT, increase knowledge of stunting prevention with local food and biofloc pond catfish cultivation and PMT processing skills with local food and biofloc pond catfish cultivation in PKK groups. The implementation method is through providing education and training. PODKESAD is able to increase the knowledge of PHBS KAT (76.2%) and behavior (77.9%), increase the knowledge of PKK groups about preventing stunting by utilizing local food (86.1%) and skills (100%), and increase the knowledge of PKK groups about catfish cultivation in biofloc ponds (83.21%) and skills (100%). It is hoped that the Hajran Village government will provide guidance for the sustainability of the program in KAT and TP PKK so that the risk of stunting can be reduced through PHBS habits and the provision of additional food and access to a variety of high-protein foods in the form of catfish floss.